Pengaruh Credit Risk Management Pada Financial Performance Bank Konvensional Yang Terdaftar Di BEI - Ervina; Vivi Nur Fatimah; Henny Setyo Lestari (Jurnal Ekonomi, 2021)
The purpose of this study is to analyze the impact of credit risk management on the financial performance of Indonesian conventional banks in 2016-2020. The sample in this study was 32 conventional banks from 160 observations using the purposive sampling technique and secondary data. The dependent variable in this paper is measured by profitability using the return on assets proxy while credit risk management is an independent variable. From the research results, LDR and NPLR have no effect on financial performance. CAR has a positive influence on financial performance so that bank managers are expected to be able to maintain their capital adequacy ratio in accordance with the provisions set by Bank Indonesia to maintain their financial performance because a high capital adequacy ratio is considered safe and tends to meet its financial obligations, while CIR and LDR negative effect on financial performance. Increasing the ratio of costs to income indicates a low level of efficiency in banking operational costs, and low liquid assets will increase cash reserves to reduce liquidity risk. Investors can invest their funds in banks that have a high capital adequacy ratio, cost of income ratio and liquidity ratio to avoid financial risk.